E-COMMERCE APPLICATION IN ORDERING FLOWER BOUQUETS USING THE RUP (RATIONAL UNIFIED PROCESS) METHOD - Yani, Desri; Sari, Adika May; Suryani, Desy; Rosmita, Rosmita; Rafik, Ahmad (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
E-commerce is an online sales application that makes it easier for customers to buy and sell in cyberspace or via the internet. Application for utilizing e-commerce in ordering flower bouquets using the RUP (Rational Unified Process) method. The RUP method is Rational Unified Process (RUP) which is a software engineering method that was developed by collecting various best practices found in the software development industry.